Towards Environmental Sustainability in Marine Finfish Aquaculture - Carballeira Braña, Carlos Brais; Cerbule, Kristine; Senff, Paula; Stolz, Insa Kristina (Frontiers in Marine Science, 2021)
Aquaculture is one of the fastest growing food production sectors and has great potential for food security and livelihoods. However, it generates concerning consequences for the environment, including chemical and biological pollution, disease outbreaks, unsustainable feeds and competition for coastal space. Recent investigations are focusing on sustainable techniques (e.g., polyculture, offshore facilities) to improve the relationship between the industry, environment and society. This review provides an overview of the main factors of ecological concern within marine finfish aquaculture, their interactions with the environment, and highlights sustainable alternatives that are currently in use or development. Adequate environmental monitoring and location of farms, the reduction and exploitation of wastes and chemicals being used is crucial to ensure the growth and continuity of aquaculture production.